Physicochemical characterization of Ni-Al2O3 and La-promoted Ni-Al2O3 catalyst for methane dry reforming - Norzaini, Abd. Rahim (2013)
The CO2 reforming reaction of CH4 was conducted by using a Ni-based catalyst were prepared by the wet co-impregnation using nickel and lanthanum on alumina support. Monometallic catalyst of 10wt.%Ni-90wt.%Al2O3 was promoted with 3wt.% lanthanum metal. The physicochemical of catalysts were characterized by XRF, FTIR, BET, and XRD respectively, which to compare the catalyst between the calcined catalyst of unpromoted (10wt.%Ni-90wt.%Al2O3) with 3La promoted (3wt.%La-10wt.%Ni-87wt.%Al2O3) performance for methane conversion to hydrogen. XRF analysis for the main metals presented in the calcined catalyst indicated a good agreement with the intended formula. FTIR analysis confirmed the presence of similar structural unit and formation of identical chemical moieties of the unpromoted and 3La promoted catalysts. XRD analysis confirmed the presence of major crystalline unpromoted catalysts is spinel (NiAl2O4) because it is formed by the reaction of Al2O3 with NiO at the higher calcination temperature of the catalyst. The physical attributes for unpromoted and 3La promoted catalyst showed a Type IV isotherm, in an indication typical of capillary condensation in mesoporous with high energy of adsorption and a hysteresis loop of Type H1 under new classification system revealing cylindrical pore geometry or spheroidal particles with reasonably uniform size. BET analysis confirmed that no discernible effect for lanthanum addition to the unpromoted bimetallic catalyst. Also, the similarity between the distribution of average Horvat & Kavazoe desorption pore size for the unpromoted and 3La promoted. Based on this analysis, I can conclude that the modified catalyst with lanthanum metal is one catalyst that will be reducing the formation of carbon on the surface catalyst during this process.